Analysis of Applications of Object Orientation to Software Engineering, Data Warehousing and Teaching Methodologies - Saha, Biswajit; Mukherjee, Debaprasad (International Journal of Computer Sciences and Engineering, 2025)
Object oriented software engineering concepts are one of the most popular methods in the information technology industry and academia as well as in many other forms of engineering design. Software engineering is a field of engineering that came into existence owing to the various problems that developers of software faced while developing software projects. This paper analyzes some of the most important technological innovations in object oriented software engineering in recent times. The advancements in Object technologies that have been analyzed here include module coupling metrics, software up gradation, layered reusability, monitors, attribute objects, global software development contexts, software testing, recursive types, coupled and co-evolving classes, query-able source codes, meta-model for generating design alternatives, programming micro-worlds, design pattern detection, object schema migration, functional verification, work system theory, and state chart diagrams. From our analysis we predict further advancements in object technologies towards game development, metrics for software design analysis, addition to fundamental Object oriented programming language features and distributed software engineering.